Pemberdayaan Masyarakat Desa Mekargalih Kec. Jatiluhur Melalui Sedekah Minyak Jelantah - Jalaludin, Jalaludin (STIE Syariah Indonesia Purwakarta, 2022)
Most of the waste in Mekargalih village is still not managed properly so it becomes a phenomenon that is quite complicated to solve. So that waste that is not managed properly becomes a hotbed for the spread of disease and causes environmental pollution. The Used Cooking Oil Alms Program is carried out so that the community can care about the environment, as well as a creative program that tackles the problem of B3 waste. The purpose of PKM is to empower the village community in Mekargalih Kec. Jatiluhur through the alms of used cooking oil trains the community and provides knowledge to develop their potential, both natural potential and the potential that exists within the community to lead to awareness and concern for both the community and village government towards environmental cleanliness which is implemented in the example of using waste and oil. used. Conclusion of PKM on Community Empowerment in Mekargalih Village, Kec. Jatiluhur Through this Waste Cooking Oil Alms, the community has the knowledge that used cooking oil can become waste that is harmful to the environment because it can pollute clean water and soil. In addition, the people of Mekargalih village are more concerned about the environment not to throw used cooking oil carelessly, many people are even aware that used cooking oil can produce various products that are useful in their daily lives, when compared to throwing it directly on the ground. Furthermore, from the PKM support program, the community feels helped by the community service program, on the other hand as a means to get closer to the community, on the other hand community service can strengthen brotherhood among the residents of the Mekargalih village, Jatiluhur Purwakarta.